Effect of Well Resistance on Time Factor Ratio Due to PVD Deformation - Galuh Chrismaningwang; Hary Christady Hardiyatmo; Agus Darmawan Adi; Teuku Faisal Fathani (Journal of the Civil Engineering Forum, 2021)
One of the most common soft soil enhancement techniques used to expedite the consolidation time significantly is Prefabricated Vertical Drains (PVD). This technique needs a sufficient discharge capacity value because it primarily functions as a drainage channel. The deformation of PVD is considered as one of the primary factors which affect discharge capacity. Therefore, this research determined the influence of upper-side deformation on PVD's discharge capacity (qw) using a specific design apparatus known as ASTM D4716, which manages the determination of transmissivity and flow rate at the longitudinal direction of geosynthetics. Furthermore, two PVD samples with dimensions of 3 and 4 mm thickness, 100 mm width, and 1000 mm length were examined under straight and buckled conditions. Stepwise confining pressures from 50 to 200 kPa were subjected to the samples under hydraulic gradients with values of 0.2, 0.5, and 1.0. The results showed that samples with greater thickness had higher discharge capacity, which significantly reduced in the lower hydraulic gradient. The deformation on the upper side of PVD induced a decrease of discharge capacity by approximately 13-16%, which led to a delay in the consolidation time. The discharge capacity values obtained from the experiments were employed as parameters in a time factor ratio of Th,w/Th. The analysis results show that the buckled PVD has a more considerable consolidation time due to the increase in the Th,w/Th ratio, with a discharge capacity value below 10-4 m3/s. It can be concluded that the deformation in the form of buckled conditions on the upper side of PVD had a considerable impact on PVD effectiveness.